Relationship between the magnitude of IgE production in mice and conformational stability of the house dust mite allergen, Der p 2 - Nakamura, Hitomi; Ohkuri, Takatoshi; So, Takanori; Ueda, Tadashi (Biochimica et biophysica acta, 2016)
Protein antigens are degraded by endosomal protease in antigen presentation cell. T cells recognize peptides derived from antigen proteins bound to class II major histocompatibility complex molecules. We previously reported that an increase in the conformational stability of an antigen depressed its immunogenicity. However, there is little information on antigens with differences in molecular properties such as net charges and molecular weight. Denaturation experiments against guanidine hydrochloride. The serum IgE levels to protein antigens at 35days after the first immunization analyzed using ELISA. The Der p 2 mutations in which Ile13 is mutated to Ala (I13A) and Ala122 is mutated to Ile (A122I) were shown to have lower and higher conformational stability than the wild-type, respectively, by denaturation experiments. The amount of IgE production by the less stable I13A mutant was higher and that of the stable A122I mutant was lower than that of the wild-type. Our results suggest that the increased conformational stability of Der p 2 depressed the IgE production in mice. These findings should provide a milestone for the engineering of allergen vaccines. •Conformational stability of Der p2 relates to its immunogenicity.•Stabilization of Der p2 depresses the IgE production in mice.•Conformational stability of a protein may be closely involved in preparing vaccines.